Proceedings of the Thirteenth ACM Symposium on Operating Systems Principles 1991
DOI: 10.1145/121132.344329
|View full text |Cite
|
Sign up to set email alerts
|

First-class user-level threads

Abstract: It is often desirable, for reasons of clarity, portability, and efficiency, to write parallel programs in which the number of processes is independent of the number of available processors. Several modern operating systems support more than one process in an address space, but the overhead of creating and synchronizing kernel processes can be high. Many runtime environments implement lightweight processes (threads) in user space, but this approach usually results in second-class status for threads, making it d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(31 citation statements)
references
References 15 publications
0
30
0
1
Order By: Relevance
“…Several operating systems have explored issues related to performance and scalability on multi-processor platforms [1][17] [18][19] [20]. While the McRT framework is similar in spirit to these projects and learnt from their experiences, it is more lightweight and had to address significant differences in the underlying hardware.…”
Section: Related Workmentioning
confidence: 99%
“…Several operating systems have explored issues related to performance and scalability on multi-processor platforms [1][17] [18][19] [20]. While the McRT framework is similar in spirit to these projects and learnt from their experiences, it is more lightweight and had to address significant differences in the underlying hardware.…”
Section: Related Workmentioning
confidence: 99%
“…In general, the lock holder preemption problem can be solved either by prevention-or recovery-based solutions ( [3,18]). Prevention-based solutions notify user-level threads about imminent preemption.…”
Section: Coordination Between the Operating System And User-level Thrmentioning
confidence: 99%
“…" Trends in operating system research suggest that most of the resource allocation and process management software should be moved out of the operating system kernel [46,4,53], and implemented in user-level servers instead. The operating system only provides the basic mechanisms to tie the system together.…”
Section: The Solution •mentioning
confidence: 99%
“…Several studies have shown that this effect can lead to severe performance degradation [45,48,49,721. For this reason, some systems incorporate a special mechanism to avoid preemption while in a critical section [4, 28,53] In addition, Squillante and Lazowska [66,67] have shown that by ignoring the affinity 0 that may have been created between a process and a processor, a centralized ready queue can introduce a performance penalty close to a factor of two This penalty is attributed to cache reload costs and increased bus traffic and contention overheads. They propose a scheduling mechanism that avoids migrating processes unless significant imbalance occurs.…”
Section: Multiprogramming Techniques •mentioning
confidence: 99%
See 1 more Smart Citation